Ovarian torsion as an unusual presentation of primary bilateral ovarian lymphoma - Mohammed Azfar Siddiqui; Sara Sartaj; Syed Wajahat Ali Rizvi; Iraj Alam Khan (Indian Journal of Medical and Paediatric Oncology)
Primary ovarian involvement by Burkitt's lymphoma is rare and accounts for 0.5% of nonHodgkin lymphoma and 1.5% of ovarian tumors. We herein describe a very rare case of primary bilateral ovarian lymphoma in a 14-year-old presenting as ovarian torsion.